DEVELOPMENT OF DISTANCE LEARNING TECHNOLOGY WITH SMART CAMPUS IN IMO CONVENTION SUBJECT IN THE COVID-19 PANDEMIC AT MALAHAYATI MERCHANT MARINE POLYTECHNIC - Rispa Saeful Mu'tamar; Fazri Hermanto (Penerbit Lafadz Jaya, 2022)
Pandemic Covid-19 in 2022 will continue and of course bring changes to the habits of human life in the world, especially in Indonesia, these changes bring new habits to human activities that make them study, work and worship from home, this certainly brings changes to the learning system that implemented in every educational institution that brings changes to the learning system, namely the Distance System. In 2021 the Malahayati Merchant Marine Polytechnic will develop a new distance learning technology called the Smart Campus. The development can provide convenience for various parties, namely students, educators, and education staff responsible for the implementation of the distance learning system at the Malahayati Merchant Marine Polytechnic. The purpose of this study was to examine in terms of the effectiveness of using a smart campus as a technology in the implementation of distance learning, it certainly wanted to observe the relation to the learning achievement of students and the activeness of lecturers in implementing distance learning using a smart campus. This research method uses This study uses a descriptive qualitative approach. The data collection methods that will be used in the study are interviews, questionnaires, observation, and documentation. To test the hypothesis, a multiple regression measuring instrument (multiple regression) will be used where the amount of Y (learning achievement) quantitatively will be known from each variable X. The results of this study show that based on the results of the study, the calculated > Ftable > 2,311] at the significance level 50,725 = 5%, it states that simultaneously (together) the smart campus application variable affects the learning achievement of participants studied at the Malahayati Merchant Marine Polytechnic.